Influence of Hot Extrusion and Aging Treatment on the Properties of Biodegradable Mg-Zn-Y Alloy. Issue 3 (March 2018) - Xueyan, Qiao; Kun, Yu; Liangjian, Chen; Yilong, Dai; Tao, Xiao; Youwen, Deng; Yang, Yan
Abstract : Abstract: Mg-6Zn-1Y (mass fraction, %) alloys were prepared for degradable biomaterials. The billets of the alloy were produced by powder metallurgy (PM) method and then hot extruded. The extruded samples were aged for 24 and 72 h at 150 °C. The microstructure and corrosion behavior of the experimental alloys were investigated. The microstructure observations indicate that the alloys contain α -Mg, MgZn, MgZn2 and Mg3 YZn6 (I-phase) phases. The hot extrusion process significantly refines the grains and leads to better mechanical properties with the value of compressive strength in the range of 365∼399 MPa, and better corrosion resistance for the PM alloy shows higher hydrogen volume in the immersion test. Furthermore, due to more uniform corrosion behavior, the alloy aged for 72 h presents lower corrosion rate and corrosion current density in the immersion test and potentiodynamic polarization test, and higher resistance value ( R p ) results from the electrochemical impedance spectroscopy (EIS), which means the alloy aged for 72 h exhibits better corrosion resistance than the other three alloys.